Fetal cardiomegaly: A rare presentation of parkes weber syndrome - Niraj Kumar Dipak; Ruchi Nimish Nanawati; Saumil Desai; Anita Ananthan (Wolters Kluwer Medknow Publications, 2017)
Vascular malformations (VMs) are developmental abnormalities of the vascular system. VM can be divided into high flow (predominantly arteriovenous malformations) and low flow (capillaries, venous, lymphatic, and mixed). VMs may present antenatally, at birth, or may develop during childhood. The presence of high-flow lesion on Color Doppler favors the diagnosis of Parkes Weber syndrome (PWS) over Klippel-Trenaunay syndrome. The management of high output failure, skin, and orthopedic care remains the mainstay of therapy in PWS. We report a fetus with highly vascular swelling over left upper limb, which was detected when fetal cardiomegaly was alerted and looked out for its possible etiology. Fetal cardiomegaly demands meticulous sonographic screening of extremities of fetus as they often get missed.